Targeting MAIT cells as a cellular adjuvant for humoral immunity: a new player in a very old game - Provine, NM (Wiley, 2023)
In this article, I discuss recent work by Pankhurst et al. They found that MAIT cells can serve as a cellular adjuvant to boost immunity to a protein adjuvant. Intranasal co-administration of protein antigen with a strong MAIT cell ligand results in the the production of mucosal IgA and IgG antibody responses. This process is driven by MAIT cell-mediated maturation of migratory dendritic cells.